Exploring caregiver experiences and support needs in end-of-life care for people living with HIV: A scoping review protocol. - Kristina M Kokorelias; Andrew D Eaton; Marina Wasilewski; Tyler Redublo; Luxey Sirisegaram (PLoS ONE)
Background and objectives End-of-life care supports individuals in the last few weeks or months of their life and their caregivers, offering psychosocial support, symptom management and relief, and resources. While some of the first public end-of-life care facilities were established due to HIV/AIDS, the current needs of caregivers for people living with end-stage HIV are not well understood. Caregivers provide two-thirds of the care for people living with HIV, yet their specific support needs and experiences are under-researched. Existing strategies often use a "one-size-fits-all" approach, which may not address the unique challenges faced by these caregivers, such as stigma and lack of social support. This study aims to synthesize the literature on the end-of-life care experiences and needs of caregivers for individuals living with HIV. Research design and methods A scoping review, guided by Arksey and O'Malley's framework and the Joanna Briggs Institute's recommendations, will be conducted. An Information Specialist will assist in developing a search strategy to be applied across databases like Medline, Embase, PsycINFO, and PubMed. Search results from each database will be imported into Covidence software for duplicate removal and title and abstract screening. Two researchers will independently screen studies using the 'Population-Concept-Context' (PCC) framework, with screening conducted at two levels: title and abstract, and full-text. The inclusion criteria will be piloted on a random sample of articles to ensure inter-rater agreement (kappa statistic >0.61). Disagreements will be resolved through discussion or with the involvement of a content expert if needed. Final selections will be reported using the PRISMA flow diagram, and reasons for exclusion will be documented. Discussion and implications The findings from this scoping review will provide valuable insights into the end-of-life care experiences and support needs of caregivers for individuals living with HIV. By identifying common themes and challenges, such as caregiver fatigue, emotional strain, stigma, and lack of social support, this study will underscore the inadequacy of the current "one-size-fits-all" approach in addressing the unique needs of these caregivers. This research has the potential to influence both clinical practice and policy by advocating for more personalized support strategies within end-of-life care settings.